AI dan Guru di Dunia Pendidikan: Bukan Kompetisi, tapi Kolaborasi - Nuha, Muhammad Ullin; Atikoh, Nurul; Safitri, Maulida; Khoiriyah, Ummatul; Alhasan, Sudap (Sosaintek: Jurnal Ilmu Sosial Sains dan Teknologi, 2024)
Advances in technology, particularly artificial intelligence (AI), have had a significant impact on education. However, instead of replacing teachers, AI should be seen as a partner that can enrich the teaching and learning process. This research aims to explore how AI can support teachers in creating a more personalised and effective learning experience. The research method used was a literature study and in-depth interviews with educators to understand the perceptions and challenges of AI integration in the classroom. The results show that AI has great potential in supporting learning through personalisation of materials, analysis of student learning data, and reduction of teachers' administrative burden. However, this collaboration will only be successful if there is adequate training for teachers as well as an ethical approach in the application of such technology.